The meaning of emotion as related to human conduct - Buckman, Ruby M. (My University, 1908)
Introduction: Until recently the psychology of states of feelings or emotions has been in what might be called a backward condition. As compared with other phases of psychology, especially in view of the importance of the part played by emotions in human life, it has scarcely received due consideration.
Citation: Buckman, Ruby M. The meaning of emotion as related to human conduct. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Psychology; Emotions; Conduct; Graduating theses; Senior theses; Theses